A Study of the Impact of Micro-Aggressions on the Culture of Respect, Job Performance and Retention at a Workplace - Monica Kunte; Aastha Verma; Prateek Singh Bhadauria; Mohit Somani (Australasian Accounting, Business and Finance Journal, 2025)
This study aims to investigate the prevalence and impact of microaggressions approach; the first phase involved quantitative surveys of the employees, and the second phase involved face-to-face interviews with the sampled employees. The participants were requested to describe the microaggressions that they encountered, including the frequency, the nature of the incidents, and the consequences that were realised. Age, gender, and employment position were also included in the demographic information that was sought. The findings indicate that microaggressions are common across the identified demographic attributes and that there could be some variations in the rates and types of microaggressions based on such criteria. Notably, it was established that age and gender prejudice microaggression was common, as depicted by the participants. Thus, the study calls for further research to discover a complex interconnection between microorganisms, organisational culture, and performance outcomes. From the study, it is evident that there should be an understanding of microaggressions in organizations for there to be a change and establishment of equal opportunities for all. Future research should try to elucidate the relationships between microaggressions, organizational culture, and performance results. Therefore, this study contributes to the existing literature by filling a gap in a comprehensive analysis of microaggressions in a certain context of working environment. The implications of the study are useful for organisations interested in enhancing their culture and examining the effects of microaggressions on employees.
Keywords: Microaggressions; Workplace Culture; Employee Turnover; Productivity; Diversity & Inclusion; Job Satisfaction; Team Collaboration; Talent Retention